Thrombin generation assays to personalize treatment in bleeding and thrombotic diseases - Valke, Lars L. F. G.; Rijpma, Sanna; Meijer, Danielle; Schols, Saskia E. M.; van Heerde, Waander L. (Frontiers in Cardiovascular Medicine, 2022)
Treatment of bleeding and thrombotic disorders is highly standardized and based on evidence-based medicine guidelines. These evidence-based treatment schemes are well accepted but may lead to either insufficient treatment or over-dosing, because the individuals’ hemostatic properties are not taken into account. This can potentially introduce bleeding or thrombotic complications in individual patients. With the incorporation of pharmacokinetic (PK) and pharmacodynamic (PK-PD) parameters, based on global assays such as thrombin generation assays (TGAs), a more personalized approach can be applied to treat either bleeding or thrombotic disorders. In this review, we will discuss the recent literature about the technical aspects of TGAs and the relation to diagnosis and management of bleeding and thrombotic disorders. In patients with bleeding disorders, such as hemophilia A or factor VII deficiency, TGAs can be used to identify patients with a more severe bleeding phenotype and also in the management with non-replacement therapy and/or bypassing therapy. These assays have also a role in patients with venous thrombo-embolism, but the usage of TGAs in patients with arterial thrombosis is less clear. However, there is a potential role for TGAs in the monitoring of (long-term) antithrombotic therapy, for example with the use of direct oral anticoagulants. Finally this review will discuss controversies, limitations and knowledge gaps in relation to the introduction of TGAs to personalize medicine in daily medical practice.